1999
DOI: 10.1093/ajcn/69.3.403
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 2 low-fat stanol ester–containing margarines on serum cholesterol concentrations as part of a low-fat diet in hypercholesterolemic subjects

Abstract: We conclude that the low-fat, plant stanol ester-containing margarines are effective cholesterol-lowering products in hypercholesterolemic subjects when used as part of a low-fat, low-cholesterol diet. They offer an additional, clinically significant reduction in serum cholesterol concentrations to that obtained with a low-fat diet alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
99
1
10

Year Published

2000
2000
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(117 citation statements)
references
References 23 publications
7
99
1
10
Order By: Relevance
“…This result is similar to those of earlier studies, in which plant stanol esters (2-3 g/day of plant stanols) have reduced LDL-C by 9-15% (Vanhanen et al, 1993;Gylling and Miettinen, 1994;Gylling et al, 1995Gylling et al, , 1997Gylling et al, , 1999Miettinen et al, 1995;Hallikainen and Uusitupa, 1999;Hallikainen et al, 2000a;Mensink et al, 2002). Our result also confirms the fact that plant stanol ester does not affect serum HDL-C or TG.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This result is similar to those of earlier studies, in which plant stanol esters (2-3 g/day of plant stanols) have reduced LDL-C by 9-15% (Vanhanen et al, 1993;Gylling and Miettinen, 1994;Gylling et al, 1995Gylling et al, , 1997Gylling et al, , 1999Miettinen et al, 1995;Hallikainen and Uusitupa, 1999;Hallikainen et al, 2000a;Mensink et al, 2002). Our result also confirms the fact that plant stanol ester does not affect serum HDL-C or TG.…”
Section: Discussionsupporting
confidence: 93%
“…Thus one can with confidence claim that the reduction in serum lipids in the stanol group was almost certainly owing to the plant stanols. The daily intake of plant stanol was 2 g, which was, on the basis of the earlier studies (Vanhanen et al, 1993;Gylling and Miettinen, 1994;Gylling et al, 1995Gylling et al, , 1997Gylling et al, , 1999Miettinen et al, 1995;Hallikainen and Uusitupa, 1999;Hallikainen et al, 2000a;Mensink et al, 2002), estimated to be adequate.The daily dose of the cheese product was taken in one or two portions with main meals. It has been reported that plant stanols, either consumed once a day or divided between the meals, resulted in a similar decrease in serum lipids .…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…These effects collectively lead to the inhibition of TAG synthesis and consequently the reduction of plasma TAG levels. A great body of evidence demonstrates that PS supplementation has no effect or tends to increase plasma TAG levels [21,24,25,[29][30][31][32][54][55][56][57]. When BBR was co-administered with PS, an additive effect of BBR and PS on plasma TAG was observed.…”
Section: Discussionmentioning
confidence: 99%
“…It was also expected that BBR and phytosterols would decrease plasma TAG levels when provided in combination. Because plant sterols, stanols, and their ester forms possess similar capacities to lower circulating cholesterol [23][24][25][28][29][30][31][32][33][34][35][36][37], in the present study we have chosen the stanol form of phytosterols (PS) to determine the effect of combined treatment of BBR and PS on plasma cholesterol and TAG concentrations in rats fed a high-fat and high-cholesterol diet. The safety/toxicity of BBR and PS was evaluated by hepatic biochemical parameters that are routinely used in basic toxicological research and the clinical diagnosis of drug/chemical-induced toxicity.…”
Section: Introductionmentioning
confidence: 99%